Pengetahuan dan Sikap Ibu terhadap Pemberian ASI Eksklusif di Wilayah Kerja Puskesmas Simpang Kawat - Nurbaiti Nurbaiti (Jurnal Akademika Baiturrahim Jambi, 2021)
Breast milk contains colostrum which is rich in antibodies because it contains proteins for endurance and high amounts of germ killer so that exclusive breastfeeding can reduce the risk of death in babies and can prevent malnutrition and stunting in babies, at this time there are still mothers who do not give breast milk exclusively because the mother works outside the home so that the mother can not breastfeed her baby properly and regularly, knowledge and attitude is important in supporting the success of exclusive breastfeeding where if the mother's knowledge is good and the attitude is positive then the mother can give breast milk exclusively. The purpose of this study is to find out the knowledge and attitude of mothers towards exclusive breastfeeding. This study uses an descriptif  research design, The population of this study is mothers who have babies aged 0-24 months at Puskesmas Simpang Kawat Jambi. Sample amounted to 42 respondents. This research instrument uses questionnaires and uses informed consent sheets.  The results of this study showed that of the 42 respondents, most of the mothers had good knowledge, namely 29 people (69.0%), while those who had enough knowledge as many as 13 people (31.0%), and who had a positive attitude of 28 people (66.7%) while those with negative knowledge as many as 14 people (33.3%) conclusion of this study, mothers are well known and have a positive attitude towards exclusive breastfeeding.